Analysis of Land Surface Temperature in Buru Regency Using MODIS Satellite Imagery Data Based on Cloud Computing with Google Earth Engine - Rakuasa, Heinrich; Sihasale, Daniel Anthoni (Program Studi Pendidikan Geografi FKIP Universitas Pattimura, 2023)
Monitoring land surface temperature in Buru Regency using geospatial technology based on Google Earth Engine cloud computing can help in understanding climate and weather changes on a global scale, as well as provide essential information for scientists, governments, and non-governmental organizations in making decisions related to climate change mitigation and disaster management. This study aims to analyze land surface temperature in Buru Regency using MODIS satellite imagery data based on Google Earth Engine cloud computing. The research utilizes Moderate Resolution Imaging Spectroradiometer (MODIS) Terra Land Surface Temperature and Emissivity 8-Day Global data, accessed and analyzed through Google Earth Engine. The lowest land surface temperature in Buru Regency is 12.7438°C, and the highest is 31.9582°C. The area with very high land surface temperature (LST) covers 96,604.46 hectares, or 19.90%; high LST covers 139,606.47 hectares or 28.76%; medium LST covers 140,853.38 hectares, or 29.02%; low LST covers 79,896.56 hectares, or 16.46%, and very low LST covers 28,458.57 hectares or 5.86%. The analysis of land surface temperature in Buru Regency can provide crucial information for the local government in policy-making and planning for sustainable regional development.